Longitudinal surveillance and analysis of antimicrobial resistance in bovine pathogens in North Gujarat: an 18-month perspective - Janki Panchal; Sandip Patel; Arun Patel; Harshad Chauhan; Kishan Sharma; Milan Dabhi; Mehul Shrimali; Sushil Mohapatra; Aakash Thakore; Jignesh Prajapati; Dweipayan Goswami (Discover Applied Sciences)
Abstract Antimicrobial resistance (AMR) is a growing concern in veterinary and human medicine, impacting treatment efficacy and public health. This 18-month longitudinal study monitored AMR trends in bovine mastitis pathogens in the Banaskantha district of North Gujarat, India. A total of 424 bacterial isolates were analyzed following Clinical and Laboratory Standards Institute (CLSI) guidelines, with bacterial identification using MALDI-TOF mass spectrometry, and data analysed through the World Health Organization (WHO) WHONET software. Escherichia coli and Staphylococcus aureus were the most prevalent pathogens, exhibiting high resistance to cefotaxime/clavulanic acid and penicillin G, respectively. The study identified multidrug-resistant (MDR) and pan-drug-resistant (PDR) strains, raising significant treatment concerns. These findings emphasize the urgent need for ongoing AMR surveillance, responsible antibiotic use, and stricter regulations to mitigate resistance risks. A One Health approach is essential to address the interconnected threats posed by AMR across human, animal, and environmental health.